2014
DOI: 10.1159/000357759
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology of Emotion Experience in First-Episode Psychosis

Abstract: Background: Although it has been suggested that disturbances in emotion experience and regulation play a central role in the aetiology and psychopathology of schizophrenia spectrum disorders, the phenomenology of emotion experience in schizophrenia remains under-researched. Sampling and Methods: In-depth interviews were conducted twice with each of the 20 participants (firstly at admission and secondly 6 months later). Data collection and analysis were guided by the principles of phenomenological study of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
(78 reference statements)
1
26
0
2
Order By: Relevance
“…Specifically in our study, a tendency to resonate and experientially go along with negative stimuli is nonetheless accompanied by an apparent experiential disconnection between the self and the bodily resonance for positive emotions. Embodiment is a fundamental condition of selfhood Sinigaglia, 2010, 2011;Gallese and Ferri, 2013), and such disembodiment of emotion (Fuchs, 2005;Vodušek et al, 2013) we found in our study-actualized through a bodily, anomalous echo-further remarks the need to conceptualize schizophrenia as a disorder of the Self and of the Intersubjective attunement . Hence, as argued: "Schizophrenic persons undergo a special kind of depersonalization: the living body becomes a functioning body, a thing-like mechanism in which feelings, perceptions, and actions take place as if they happened in an outer space."…”
Section: Discussionsupporting
confidence: 57%
“…Specifically in our study, a tendency to resonate and experientially go along with negative stimuli is nonetheless accompanied by an apparent experiential disconnection between the self and the bodily resonance for positive emotions. Embodiment is a fundamental condition of selfhood Sinigaglia, 2010, 2011;Gallese and Ferri, 2013), and such disembodiment of emotion (Fuchs, 2005;Vodušek et al, 2013) we found in our study-actualized through a bodily, anomalous echo-further remarks the need to conceptualize schizophrenia as a disorder of the Self and of the Intersubjective attunement . Hence, as argued: "Schizophrenic persons undergo a special kind of depersonalization: the living body becomes a functioning body, a thing-like mechanism in which feelings, perceptions, and actions take place as if they happened in an outer space."…”
Section: Discussionsupporting
confidence: 57%
“…The objective of phenomenology is to answer “how is it to have a particular experience” [ 25 ]. Phenomenology as a theoretical framework is intended to precisely describe, analyse, and interpret experience from an individual point of view and is expressed as a personal story [ 26 , 27 ]. Its aim is to uncover the meaning of intensity of being, to develop a deeper understanding and a detailed identification of personal experience.…”
Section: Methodsmentioning
confidence: 99%
“…They also failed to explain why and how anxiety becomes the prodromal period of BD. From the viewpoint of psychology, anxiety is a basic emotion that can be converted or transformed into any other emotion [ 23 ]. We hypothesize that when people experience stress, the common emotion of anxiety occurs, and with the continuation of stress, this emotion gradually evolves into pathological anxiety.…”
Section: Introductionmentioning
confidence: 99%